COMMENTS TO THE LATEST EUROPEAN GUIDELINES FOR THE MANAGEMENT OF ARTERIAL HYPERTENSION (2007) - V. M. Gorbunov (Рациональная фармакотерапия в кардиологии)
Comments to the latest European Guidelines for the Management of Arterial Hypertension (2007).